Direct and Inverse Seismic Modeling Three-Dimensional Complex Geology (Journal of Computational Mathematics, 2022)
We give a brief account of recent results from a project to develop efficient algorithms and practical computer implementations for modeling complex, 3-D geological regions, with applications to exploration and general seismology. The problem is divided into geometrical and material description and visualization, forward modeling with ray tracing and finite element elastic wave propagation, and finally, least squares inversion of travel time data.